O – Level Mathematics and Science Teachers’ Alignment of STEM Skills Oriented Instructional Objectives with Assessment in a High Stakes Examinations Environment - Alois Matorevhu (International Journal of Trends in Mathematics Education Research, 2020)
In any school context, teaching and learning should be guided by objectives developed, and used by the teacher. These objectives are benchmarks by which the learning process is assessed. The teacher plays a dual role of assisting learners to develop requisite skills for the world of work, and ability to obtain good grades in high stakes examinations. High stakes examinations are of critical importance to the learner, because they determine the future of the learner through grades which are awarded. The balance between satisfying the requirements of syllabus assessment objectives, and high stakes examinations depends on how the teacher develops and implements instructional objectives. In an attempt to gain insight, this study explored O-Level mathematics and combined science teachers’ alignment of science, technology, engineering and mathematics (STEM) oriented objectives with assessment in a high stakes examinations environment. Data were collected through interviews, observations and document analysis involving 10 mathematics and combined science teachers. Results suggest that, while teachers were aware of Mathematics and Combined Science syllabus requirements of aligning STEM oriented objectives with assessment, they devoted considerable time to preparation of students for high stakes examinations. However, the quality of preparation was questionable, measured against Bloom’s Taxonomy of educational objectives. Teachers tended to use drilling methods, the aim being production of high grades in high stake examinations, with little focus on understanding and application of knowledge in real life situations. It is recommended that teachers should include higher order STEM oriented instructional objectives aligned with assessment in order to prepare learners for the real world of work.